Strict fluid volume control and left ventricular hypertrophy in hypertensive patients on chronic haemodialysis: a cross-sectional study - Gunal, AI; Karaca, I; Aygen, B; Yavuzkir, M; Dogukan, A; Celiker, H (Field House Publishing Llp, 2004)
Left ventricular hypertrophy (LVH) is very common in haemodialysis patients. We measured left ventricular mass in three groups of haemodialysis patients: group A (n = 40) were normotensive and receiving a strict salt-restricted diet; group B (n = 23) were normotensive and receiving antihypertensive drugs; and group C (n = 43) were hypertensive despite anti-hypertensive drug treatment. The interdialytic weight gain in group B and group C was significantly higher than in group A; the mean left atrial index and left ventricular end-systolic and end-diastolic diameter indices were all higher in group B than in group A. The interventricular septum and posterior wall were significantly thicker in group B and group C than group A, resulting in a higher left ventricular mass index. Left ventricular systolic and diastolic function parameters were slightly better in group A than in the other groups. These results show that strict fluid volume control decreases blood pressure, reduces dilated cardiac compartments and corrects LVH more effectively than lowering blood pressure without correcting the volume overload.
Keywords: strict fluid volume control; anti-hypertensive drugs; haemodialysis; left ventricular hypertrophy; echocardiography